Synthesis of trimetallic iron-boron core and gold shell nanoparticles for experimental cancer radiotherapy - Coward, Brad; Wang, Jiawei; Kysela, Boris (Frontiers in Bioengineering and Biotechnology, 2024)
Cancer is a significant and constantly growing clinical problem all over the world. For many types of cancer there has been little change in mortality rate of CRC in the past decades and treatment options are limited. Considerable research efforts in the last several decades have failed to improve these outcomes. Boron Capture Neutron Therapy (BNCT) is an experimental radiotherapy (RT) that shows the best hope for the patients for whom all current therapies fail. BNCT involves the intracellular release of alpha and Li-ion particles from boron in response to neutron beam and therefore its success is critically dependent on achieving high intracellular concentrations of boron atoms within the cancerous cells. Boron phenylalanine is the most used compound to deliver boron atoms, but achieving high intracellular concentration of BPA is difficult with this small molecule compound and is an absolute limiting factor for the better outcome of BNCT. Our approach focused on a delivery of a high and stable concentration of boron atoms in a form of novel trimetallic core-shell nanoparticles, combining boron for BNCT and iron for magnetic targeting in the core, and a gold shell for stability and attachment of targeting therapeutic peptides. The research was targeted towards comparing different synthesis variables to form these core-shell particles and incorporate as much boron into the core as possible via redox-transmetalation. Partial gold shells were formed around the core via island growth with a molar ratio of Fe/B of 0.64 and high incorporation of boron.